A Systematic Review of Self-Management Interventions for Patients with Colorectal Cancer - Aryani, Ratna; Huda, Mega Hasanul; Lalisang, Toar JM; Dahlia, Debie; Martha, Evi; Wicaturatmashudi, Sukma; Sukarmin, Sukarmin (The Malaysian Journal of Nursing (MJN), 2025)
Background: Colorectal cancer (CRC) is a major global health issue and ranks among the most prevalent cancers worldwide. Despite treatment advancements, CRC patients often encounter challenges that negatively impact their QoL, highlighting the need for effective self-management strategies. Objective: This systematic review assesses the types, content, and impacts of self-management interventions for CRC patients. Methods: A systematic review was conducted, reviewing studies published between January 2013 and February 2022, across nine databases, including JSTOR, Emerald Insight, Oxford Academic, ScienceDirect, SAGE, Clinical Key, ProQuest, Scopus, and Taylor & Francis. The review focused on randomised controlled trials (RCTs) involving self-management strategies for adult CRC patients. Keywords used included "colorectal cancer," "colorectal survivor," "bowel cancer," "colorectal tumour," "colorectal neoplasm," "self-management programme," "self-management training," "self-management intervention," "randomised controlled trial," and "experimental study." Articles were selected based on title and abstract relevance, and findings were synthesised narratively and tabulated. Results: The search yielded 668 articles, with nine studies included after screening and bias risk assessment. Interventions varied, lasting from 24 days to 12 months, with assessments conducted 3-4 times. These included psycho-educational programmes, smartphone apps, supportive care, self-help workbooks, access to e-Health resources, and structured pain self-management. Control groups generally received standard care or the same intervention post-study. Outcomes included improvements in self-efficacy, QoL, distress, anxiety, depression, physical activity, adherence to medical advice, symptom management, functional scales, emotional and social functioning, patient competence, social support, and pain management. Conclusions: Self-management interventions for CRC patients significantly enhance various health outcomes, underscoring their potential to improve nursing and patient care and QoL.